2016
DOI: 10.1111/gbb.12294
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary wheel running reduces voluntary consumption of ethanol in mice: identification of candidate genes through striatal gene expression profiling

Abstract: Hedonic substitution, where wheel running reduces voluntary ethanol consumption has been observed in prior studies. Here we replicate and expand on previous work showing that mice decrease voluntary ethanol consumption and preference when given access to a running wheel. While earlier work has been limited mainly to behavioral studies, here we assess the underlying molecular mechanisms that may account for this interaction. From four groups of female C57BL/6J mice (control, access to two-bottle choice ethanol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 110 publications
(185 reference statements)
1
19
0
Order By: Relevance
“…For example, continuous access to a wheel prior to and following each self-administration session prevents escalation of methamphetamine intake and decreases its reinforcing effects in male rats (9). Similar results have been obtained for the effects of concurrent wheel access on escalation of cocaine self-administration in adolescent female rats (44), and free-access alcohol consumption in female mice (3839), indicating that exercise attenuates/blocks the development of features of substance use disorder. As in humans, however, effects on alcohol consumption in males are variable with results from one study showing decreased consumption (37), and another, showing no effect (39).…”
Section: Overview Of Recent Findings In Male and Female Animalssupporting
confidence: 81%
See 1 more Smart Citation
“…For example, continuous access to a wheel prior to and following each self-administration session prevents escalation of methamphetamine intake and decreases its reinforcing effects in male rats (9). Similar results have been obtained for the effects of concurrent wheel access on escalation of cocaine self-administration in adolescent female rats (44), and free-access alcohol consumption in female mice (3839), indicating that exercise attenuates/blocks the development of features of substance use disorder. As in humans, however, effects on alcohol consumption in males are variable with results from one study showing decreased consumption (37), and another, showing no effect (39).…”
Section: Overview Of Recent Findings In Male and Female Animalssupporting
confidence: 81%
“…Recent studies also show that exercise can block drug use escalation (9,3839,44). For example, continuous access to a wheel prior to and following each self-administration session prevents escalation of methamphetamine intake and decreases its reinforcing effects in male rats (9).…”
Section: Overview Of Recent Findings In Male and Female Animalsmentioning
confidence: 99%
“…Consistent with this idea is that mice do not need to run to acquire any necessary resources (food, mating, etc. When we compared our DEG list to another RNA-seq dataset comparing the effects of wheel running and alcohol consumption on striatal gene expression in C57BL/6J mice (Darlington et al 2016), we found no significant overlap (for effects of running, P = 0.304; alcohol, P = 0.602; and interaction, P = 0.813, hypergeometric tests). If running is rewarding, and we have uncovered pathways in the brain that are associated with high motivation for running reward, then our data may inform about molecular architecture of motivation in general, or in relation to other rewards.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies in rodents have provided evidence for an interaction between voluntary wheel running and alcohol consumption . In a recent review, Hallgreen et al pointed out that, “physical exercise is widely regarded as “medicine” for the prevention and treatment of myriad somatic health conditions.” However, the effectiveness of physical activity to treat AUDs remains understudied.…”
Section: Behavioral Models Investigating the Interaction Between Wheementioning
confidence: 99%
“…Several studies have investigated the effect of voluntary exercise on 2‐bottle choice (2BC) and 2‐hour limited access drinking in the dark (DID) alcohol paradigms using unlimited access to voluntary wheel running . In an early study, Crews et al used a typical 12 day 10% alcohol 2BC paradigm and reported no effect of voluntary wheel running on male C57BL/6J alcohol consumption (females were not tested).…”
Section: Behavioral Models Investigating the Interaction Between Wheementioning
confidence: 99%